2018
DOI: 10.1123/jcsp.2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Athletes With Eating Disorders: Essentials for Best Practice

Abstract: It is estimated that 1.6 million people in the United States are currently diagnosed with an eating disorder. Eating disorders (EDs) have high rates of morbidity and mortality and remain the most severe mental illness. Unfortunately, rates of EDs and disordered eating behaviors (DEBs) among athletes appear to be increasing. In this study, authors summarize ED-related risks that pose compromises in psychological and social functioning, medical health, and overall quality of life. The importance of early detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 24 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Disordered eating is shown to have a higher prevalence among athletes than general population, even reaching 45% in female athletes [2] and this condition is especially emphasized in sports where weight controlling behaviour is expected, such as martial arts, running, synchronized swimming and gymnastics [3,4]. Moreover, patterns related to eating disorders might be difficult to detect among some athletes [5], which is a problem because eating disorder consequences are oftentimes far-reaching and could impair metabolism, bone health, cardiovascular health and mental health [6]. In addition, a decrease in food intake frequently leads to lower energy availability among athletes, a state that causes hormonal alterations, menstrual irregularities and impaired bone health, which consequently has a negative impact on sport performance as well [7].…”
Section: Introductionmentioning
confidence: 99%
“…Disordered eating is shown to have a higher prevalence among athletes than general population, even reaching 45% in female athletes [2] and this condition is especially emphasized in sports where weight controlling behaviour is expected, such as martial arts, running, synchronized swimming and gymnastics [3,4]. Moreover, patterns related to eating disorders might be difficult to detect among some athletes [5], which is a problem because eating disorder consequences are oftentimes far-reaching and could impair metabolism, bone health, cardiovascular health and mental health [6]. In addition, a decrease in food intake frequently leads to lower energy availability among athletes, a state that causes hormonal alterations, menstrual irregularities and impaired bone health, which consequently has a negative impact on sport performance as well [7].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, particularly coaches should be aware of the potential consequences when making comments that suggest an association between leanness/thinness and performance (i.e., athletes use methods to lose weight fast). Instead, coaches should educate athletes about the negative short- and long-term psychological and physiological consequences of fast and unhealthy weight loss and give appropriate advice for healthy dieting or refer athletes to an expert [9, 25, 26]. Results also indicated that athletes’ attitudes and expectations regarding an ideal body are modeled by friends and team norms.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term physiological effects such as weakness, injuries, or stress fractures impact performance. More alarming are the long-term psychophysiological consequences of an adolescent eating disorder, such as heart palpitations, dyspnea, depression, anxiety, or even suicidal thoughts, which can seriously impact an athlete’s well-being [9, 25, 26]. Therefore, and according to previous suggestions, we call for the timely screening of disordered eating and eating disorders in male and female athletes, for all types of sports, and particularly during athletes’ transition from early to late adolescence [5, 6, 17, 18, 28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations